Decline in plant species richness with a chronic decrease of precipitation: The mediating role of the dominant species - Ónodi, Gábor; Kertész, Miklós; Bede‐Fazekas, Ákos; Batáry, Péter; Kröel‐Dulay, György; Botta‐Dukát, Zoltán (The Journal of ecology, 2025)
Despite the increased frequency and severity of droughts in many regions and declining biodiversity, existing experimental evidence for changes in plant species richness associated with altered water availability is limited. The growing extent of drylands highlights the need to predict precipitation‐related changes in species richness, which requires a better understanding of the mechanisms. We carried out a field experiment applying a single extreme drought event and combined it with subsequent chronic alteration of summer precipitation for 7 years in a water‐limited temperate grassland. We assessed how altered precipitation regimes and a previous extreme drought affect species richness. We compared a simple analysis assuming only the net effect of precipitation on species richness to a complex approach by structural equation modelling that included both the direct effects of precipitation and indirect effects through the biomass of dominant grass species. Using simple analysis, we found significant positive and nonsignificant precipitation–species richness relationships in the presence and absence of extreme drought, respectively. The complex analysis disentangled direct and indirect pathways between precipitation and species richness. The indirect pathway acted only in the absence of drought. In this case, increasing precipitation increased the biomass of dominant species, which, in turn, decreased species richness, acting as a mediator variable. The direct relationship was positive, independent of the presence of drought. Synthesis. Consistent with the global relationship between water availability and species richness, we experimentally showed that decreasing precipitation decreases species richness. Furthermore, we found that increasing precipitation may also decrease plant species richness via an indirect pathway acting through the biomass of the dominant species. Our results highlight that species richness can become more sensitive to changes in precipitation after extreme drought events that eliminate or set back dominant species. In a field experiment, the authors studied how changing precipitation patterns and extreme drought affected plant diversity. Precipitation influenced species richness through direct positive effects and indirect negative effects, mediated by dominant species' biomass. Extreme drought disrupted the indirect pathway, highlighting its role. Overall, the detectability of precipitation effects on biodiversity depended on the presence of previous extreme drought.